Reconciling the discrepancies on the involvement of large-conductance Ca2+-activated K channels in glioblastoma cell migration - Catacuzzeno, Luigi; Caramia, Martino; Sforna, Luigi; Belia, Silvia; Guglielmi, Luca; D’Adamo, Maria Cristina; Pessia, Mauro; Franciolini, Fabio (Frontiers in Cellular Neuroscience, 2015)
Glioblastoma is the most common and aggressive primary brain tumor, and is notable for spreading so effectively through the brain parenchyma to make complete surgical resection virtually impossible, and prospect of life dismal. Several ion channels have been involved in glioblastoma migration and invasion, due to their critical role in supporting volume changes and Ca2+ influx occuring during the process. The large-conductance, Ca2+-activated K (BK) channels, markedly overexpressed in biopsies of patients with glioblastomas and in glioblastoma cell lines, have attracted much interest and suggested to play a central role in cell migration and invasion as candidate channels for providing the ion efflux and consequent water extrusion that allow cell shrinkage during migration. Available experimental data on the role of BK channel in migration and invasion are not consistent though. While BK channels block typically resulted in inhibition of cell migration or in no effect, their activation would either enhance or inhibit the process. This short review reexamines the relevant available data on the topic, and presents a unifying paradigm capable of reconciling all of them. According to this paradigm, BK channels would not contribute to migration under conditions where the [Ca2+]i is too low for their activation. They will instead positively contribute to migration for intermediate [Ca2+]i, insufficient as such to activate BK channels, but capable of predisposing them to cyclic activation following oscillatory [Ca2+]i increases. Finally, steadily active BK channels because of prolonged high [Ca2+]i would inhibit migration as their steady activity would be unsuitable to match the cyclic cell volume changes needed for proper cell migration.